Elevation of runaway electron current by electron cyclotron resonance heating during disruptions on J-TEXT. (11th October 2021) - Bai, W; Yan, W; Chen, Z Y; Wei, Y N; Tong, R H; Lin, Z F; Li, Y; Fang, J G; Zhang, X B; Mou, L K; Li, F; Zhang, W K; et al.
Abstract: Runaway electrons represent a serious problem for the reliable operation of future tokamaks. Radio frequency (RF) auxiliary heating can help suppress runaway electrons in the flat-top phase through a reduction in loop voltage. However, if a disruption occurs during RF auxiliary heating, it may lead to an increase in the runaway electron production due to the generation of a suprathermal population with energies in the order of ∼100 keV. The elevation of runaway current during disruptions by electron cyclotron resonance heating (ECRH) has been investigated on the J-TEXT tokamak. The results show that the conversion efficiency of runaway current increases with increased ECRH power. When the applied ECRH power is at the level of 400 kW, the conversion efficiency of Ohmic to runaway current increases from 35% to 75%, the thermal quench duration is decreased from 0.24 ms to 0.11 ms, and the Absolute Extreme Ultraviolet Spectrometer (AXUV) radiative power and electron density are about two times higher than the cases without ECRH heating.